Empowering Community Waste Management and Sustainable Practices in Paledang Village through the 4P, Vertical Garden, and PHBS Programs - Annisa, Annisa; Wandani, Ratu Aprillya; Az Zahra, Aisyah; Giovano Alfi, Dion Naldiza; Nuryantika, Fitria; Pellycia, Cheren; Syamsiyah, Sita Afrea; Yoga Pratama, Aldrichsyah; Amarulhaq, Muhamad Arham (Universitas Ahmad Dahlan, 2024)
Background: The population increase in Paledang has led to waste issues. Limited land forces many residents to use rivers as dumping sites, exacerbated by the distance and uphill terrain of waste disposal facilities. Indifference to cleanliness further sustains this behavior. Land scarcity also limits agricultural activities; Women Farmer Groups (KWT) can only farm on a 3x10 m plot, restricting crop variety and quantity. Economic challenges make it difficult for KWT to afford fertilizers, hindering their planting efforts. Contribution: Through this activity, residents of Palendang can apply their knowledge of waste processing and sorting, engage in gardening in limited spaces, and collaborate independently in the further promoted activities. Method: To address the issues mentioned above, a program called 4P (Education, Sorting, Processing, Utilization) for household waste was designed. Additionally, a vertical garden program was introduced to promote the utilization of narrow and limited spaces using walls and vertical areas. There is also a program aimed at implementing a healthy lifestyle (PHBS). Results: The results of these programs include the transfer of knowledge on waste sorting and processing into fertilizer and ecobricks, the expansion of KWT planting areas onto sloped land, as well as educational handbooks and videos that can be independently used by the community. Conclusion: Feedback from the residents of Paledang indicates that the 4P Program, vertical garden, and PHBS can be considered as alternative solutions to reduce waste and river pollution, address land and fertilizer limitations for KWT, and provide a means for socializing a clean and healthy lifestyle sustainably through the creation of guidebooks and educational videos